Medicaid home‐ and community‐based services and discharge from skilled nursing facilities. (17th June 2021) - Wang, Sijiu; Temkin‐Greener, Helena; Simning, Adam; Konetzka, R. Tamara; Cai, Shubing
Abstract: Objective: To examine the association between the generosity of Medicaid home‐ and community‐based services (HCBS) and the likelihood of community discharge among Medicare‐Medicaid dually enrolled older adults who were newly admitted to skilled nursing facilities (SNFs). Data Sources: National datasets, including Medicare Master Beneficiary Summary File (MBSF), Medicare Provider and Analysis Review (MedPAR), Medicaid Analytic eXtract (MAX), minimum data set (MDS), and publicly available data at the SNF or county level, were linked. Study Design: We measured Medicaid HCBS generosity by its breadth and intensity and described their variation at the county level. A set of linear probability models with SNF fixed effects were estimated to characterize the association between HCBS generosity and likelihood of community discharge from SNFs. We further stratified the analyses by the type of index hospitalizations (medical vs surgical events), age group, and the Medicaid cost‐sharing policy for SNF services. Data Extraction Methods: The final analytical sample included 224 229 community‐dwelling dually enrolled older duals who were newly admitted to SNFs after an acute inpatient event between October 1, 2010, and September 30, 2013. Principal Findings: We observed substantial cross‐sectional and over‐time variations in HCBS breadth and intensity. Regression results indicate that on average, a 10 percentage‐point increase in HCBS breadth was associated with a 0.7 percentage‐point increase ( P < 0.01) in the likelihood of community discharge. Such relationship could be modified by individual factors and state policies: significant effects of HCBS breadth were detected among medical patients (0.7 percentage‐point, P < 0.05), individuals aged older than 85 (1.5 percentage‐point, P < 0.01), and states with and without lesser‐of policies (0.5 and 2.3 percentage‐point, respectively, P < 0.05). No significant relationship between HCBS intensity and community discharge was detected. Conclusions: Higher Medicaid HCBS breadth but not intensity was associated with a greater likelihood of community discharge, and such relationship could be modified by individual factors and state policies.